The Life and Works of a late Ottoman Bureaucrat, Ali Fuat Turkgeldi as seen through the eyes of his son, Ali Turkgeldi, a Republican Ambassador - KENAN, SEYFİ (ISAM, 2011)
Undoubtedly, as fiber Ortayli has suggested, the 19th century, especially the period starting from Tanzimat (Reorganization) to the end of the Empire, was the longest century of Ottoman history. This article examines the life and works of a leading Ottoman bureaucrat of this late period, Ali Fuat Turkgeldi. He hailed from a bureaucratic family in which his grandfather Celal Bey had been a Tanzimat bureaucrat and his father a top official in the Translation Office. Ali Fuat Turkgeldi's works provide an important analysis of this historical period. They are examined in this article together with an unpublished biography written by his son Ali Turkgeldi, who served as the Turkish Republic's ambassador to, among other countries, India and Brazil. Ali Fuat Turkgeldi was well known for his courageous opposition to the imperial decree drawn up by the cabinet of Damad Fetid which declared Kuvay-1 Milliye a rebel force in 1919. In the last section of the article the detailed curriculum vitae written by his son is given in Latin transcription.
Keywords: Ali Fuat Turkgeldi and His Biography; Tanzimat/Re-organization; Mesrutiyet/ Constitutional Period; Ali Turkgeldi